Success factors for M-Commerce usage in Klang Valley / Elia Hasimi - Hasimi, Elia (2006)
Mobile subscribers in Malaysia began to increase and grow rapidly. Even though the latest technology was bom as 3G had wide coverage in Malaysia, mobile commerce is still in infant stage. This study is undertaken (1) to identify the level of usage in M-Commerce services among the user, (2) to identify the success factors of MCommerce usage in Klang Valley and (3) to determine the problems of MCommerce usage among the user. Mobile commerce survey has been answered by 150 respondents from a variety place and through email. The respondent was chosen randomly from the users within Klang Valley. Most of the respondents suggest minimum the m-commerce service price, wide coverage and more promotion regarding the m-commerce services. Factor analysis revealed four main success factors. The factors namely are user acceptance, the accessibility of m-commerce services, user looking for good price while using m-commerce services and the criteria of m-commerce that attract the users.